THE GROWTH OF VACHANA LITERATURE IN KARNATAKA: A STUDY (International Journal of Food and Nutritional Sciences, 2022)
Vachana literature, an integral part of Karnataka's cultural and literary heritage, emerged as a powerful tool of expression during the 12th century in the socio-religious context of the Bhakti movement. This body of literature, characterized by its devotional and philosophical themes, remains relevant to this day. Written in Kannada, Vachanas are spontaneous poetic expressions that reflect the ideas of social reformers and saints, particularly from the Veerashaiva sect, which later became known as Lingayats. The literature emphasizes spiritual awakening, the rejection of ritualistic practices, and the promotion of social equality. This paper delves into the origins, growth, and impact of Vachana literature, exploring its significance in the social and cultural history of Karnataka. It also highlights the contributions of key Vachana poets and the relevance of their works in contemporary society.